DAMPAK PANDEMI COVID-19 TERHADAP TINGKAT KESEJAHTERAANPELAKU UMKM (USAHA MIKRO, KECIL DAN MENENGAH) DI DESA DASAN TERENG KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Zulkarnaen Zulkarnaen; Muhamad Sayuti; Nurseha Midatun Hasanah (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2021)
This research is entitled "The Impact of the Covid-19 Pandemic on the Welfare Level of MSMEs (Micro, Small and Medium Enterprises) in Dasan Tereng Village, Narmada District, West Lombok Regency". The purpose of this study was to determine the impact of the COVID-19 pandemic on the welfare level of MSME actors and to provide solutions for MSME actors who still persist in entrepreneurship so that they continue to exist during the Covid-19 pandemic. This study uses a descriptive qualitative approach. Primary data collection using interview and observation techniques. The research process is carried out by comparing the income of MSME actors through three periods, namely the period before the COVID-19 pandemic, the period at the beginning of the entry of the corona virus (covid-19 pandemic), and the period after the government made a new normal program. After the author compared the income of MSME actors through the three periods, a conclusion has been drawn that the COVID-19 pandemic has indeed affected the welfare of MSME actors, this can be seen from the ups and downs of changes in the welfare status of MSME actors, which were originally the Prosperous Family III status. (KS III) before the covid-19 pandemic, then dropped to Prosperous Family I (KS I) at the time the corona virus first entered Indonesia, and after the government's new normal program, the welfare status rose to Prosperous Family II (KS III). II).